Moderate exercise based on artificial gravity preserves orthostatic tolerance and exercise capacity during short-term head-down bed rest - Li, Xiao-Tao; Yang, Chang-Bin; Zhu, Yong-Sheng; Sun, Jing; Shi, Fei; Wang, Yong-Chun; Gao, Yuan; Zhao, Jiang-Dong; Sun, Xi-Qing (Physiological research, 2017)
Numerous countermeasures have been proposed to minimize microgravity-induced physical deconditioning, but their benefits are limited. The present study aimed to investigate whether personalized aerobic exercise based on artificial gravity (AG) mitigates multisystem physical deconditioning. Fourteen men were assigned to the control group (n=6) and the countermeasure group (CM, n=8). Subjects in the CM group were exposed to AG (2 Gz at foot level) for 30 min twice daily, during which time cycling exercise of 80-95 % anaerobic threshold (AT) intensity was undertaken. Orthostatic tolerance (OT), exercise tests, and blood assays were determined before and after 4 days head-down bed rest (HDBR). Cardiac systolic function was measured every day. After HDBR, OT decreased to 50.9 % and 77.5 % of pre-HDBR values in control and CM groups, respectively. Exercise endurance, maximal oxygen consumption, and AT decreased to 96.5 %, 91.5 % and 91.8 % of pre-HDBR values, respectively, in the control group. Nevertheless, there were slight changes in the CM group. HDBR increased heart rate, sympathetic activity, and the pre-ejection period, but decreased plasma volume, parasympathetic activity and left-ventricular ejection time in the control group, whereas these effects were eliminated in the CM group. Aldosterone had no change in the control group but increased significantly in the CM group. Our study shows that 80-95 % AT aerobic exercise based on 2 Gz of AG preserves OT and exercise endurance, and affects body fluid regulation during short-term HDBR. The underlying mechanisms might involve maintained cardiac systolic function, preserved plasma volume, and improved sympathetic responses to orthostatic stress.
Keywords: Weightlessness Simulation; Humans; Head-Down Tilt; simulace stavu beztíže; Oxygen Consumption; gravitace změněná; Bed Rest; mladý dospělý; dospělí; Orthostatic Intolerance; klid na lůžku; Heart Rate; lidé; časové faktory; Adult; Trendelenburgova poloha; krevní tlak; Male; srdeční frekvence; spotřeba kyslíku; Young Adult; Exercise; ortostatická intolerance; mužské pohlaví; Gravity, Altered; cvičení; Blood Pressure; Time Factors